Circadian regulation of adipose function - Shostak, Anton; Husse, Jana; Oster, Henrik (Adipocyte, 2013)
Adipose physiology shows prominent variation over the course of the day, responding to changing demands in energy metabolism. In the last years the tight interaction between the endogenous circadian timing system and metabolic function has been increasingly acknowledged. Recent work suggests that clock and adipose function go hand in hand, regulating each other to ensure optimal adaptation to environmental changes over the 24-h cycle. In this review we describe the current knowledge on the mechanistic basis of this interaction and summarize recent findings on the impact of clock dysfunction on adipose physiology and energy homeostasis.
Published online: 13 Aug 2013
Gesehen am 27.01.2022